EDUCATIONAL TRANSFORMATION: FROM BOARDING SCHOOL TO PESANTREN WITH BI'AH ARABIYYAH - Wiza Novia Rahmi; Asti Nazhyfa; Yasmadi; Rahmawati (CV. Fahr Publishing, 2024)
This research focuses on revealing the forms and management of Arabic language culture, known as